Development of a software engineering ontology for multi-site software development - Wongthongtham, Pornpit; Chang, Elizabeth; Dillon, Tharam S.; Sommerville, I. (IEEE Computer Society, 2008)
This paper aims to present an ontology model of software engineering to represent its knowledge. The fundamental knowledge relating to software engineering is well described in the textbook titled Software Engineering by Ian Sommerville that is now in its eighth edition [1] and the white paper, SoftWare Engineering Body Of Knowledge (SWEBOK), by the IEEE [2] upon which software engineering ontology is based. This paper gives an analysis of what software engineering ontology is, what it consists of and what it is used for in the form of usage example scenarios. The usage scenarios presented in the paper highlight characteristics of the software engineering ontology. The software engineering ontology assists in defining information for the exchange of semantic project information and is used as a communication framework. Its end users are software engineers sharing domain knowledge as well as instance knowledge of software engineering.